CRESCIMENTO INICIAL DE MUDAS DE PORTA-ENXERTO DE SERINGUEIRA EM MATERIAL REFLETOR E AMBIENTES TELADOS - AGUIAR, Franciele Kelle Oliveira Moura; PAULINO, Leonardo Albino; PEREIRA, Talita Cristina Campos; COSTA, Edilson; SCALOPPI JÚNIOR, Erivaldo José; BINOTTI, Flavio Ferreira da Silva (ANAIS DO ENIC, 2018)
-